Influence of financial literacy and e-wallets on students' personal financial management in the digital era - Risdayanti Risdayanti; Asriany Asriany; Samsul Bachri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: The purpose of this study was to examine how financial literacy and e-wallet use among students at Muhammadiyah University of Palopo impact their personal financial management. This research is important because the high use of digital wallets in the digital age can impact students' financial behavior. Methodology: Quantitative and associative methods were used. Data were analyzed using multiple linear regression using SPSS after being collected from 89 participants selected through purposive sampling. Results: The results of the study showed that financial literacy had a positive and significant effect on personal financial management (t = 3.708; sig < 0.05), while e-wallets had no significant partial effect (t = 1.937; sig > 0.05). However, both variables simultaneously had a significant effect (F = 18.977; sig < 0.05) with a coefficient of determination (R²) of 0.306. Findings: The results show that financial knowledge is a major factor in how students manage their money. Novelty & Originality: Testing financial literacy and e-wallet of students in Palopo City is the focus of the latest research. This study is unique because it provides local empirical evidence in South Sulawesi. Conclusions: The result is that students need increased financial knowledge so they can use financial technology wisely. Type of Paper: This paper is an empirical research paper.